Tantangan pembelajaran online di era pandemi Covid-19 - Sunarti, Sunarti; Dini, Conita; Melania, Dyna; Izzah, Nurul (2020)
The influence of Covid-19 on the learning process has resulted in mental and cultural unpreparedness for education in Indonesia. Learning that was face-to-face (offline) now has to switch to online learning. This of course raises several challenges in online learning. This study used a research instrument in the form of a questionnaire. Several studies on online learning during the pandemic have been conducted but only focus on the impact of Covid-19 on learning. This study describes in detail the challenges faced by students in the learning process during the pandemic.